Implementation of Government Policy in Subsidising Electric Motorbike Purchases to Achieve Sustainable Environment - Nimah, Rodhotun; Sya'roni, Imam; Sutarni, Nanik (Ijtimā iyya Journal of Muslim Society Research, 2025)
Abstract The government issued a policy of an electric motorcycle purchase assistance programme through the Minister of Industry Regulation Number 21 of 2023. This policy aims to accelerate the development of the electric vehicle ecosystem in Indonesia to create a sustainable environment. Subsidising the purchase of electric motors can be considered an appropriate policy from an environmental and energy diversification perspective. Economically, such subsidies can encourage the adoption of green technologies and reduce dependence on fossil fuels. The type of research used is qualitative research using documentation data collection techniques and then analysed by reducing data, presenting data and then drawing a conclusion. This policy needs continuous monitoring and evaluation is needed to ensure that this policy is in line with the principles of a sustainable economy, including the integration of environmental, social, and economic aspects in decision-making. Are these incentives short-term or can they provide long-term economic sustainability? In further analyses, it is necessary to consider the concept of demand elasticity. The result of this study is that subsidies can increase consumer purchasing power for electric motorbikes, resulting in increased demand. However, the effect may vary depending on the price elasticity of demand. If demand is inelastic, the increase in price due to subsidies may not be proportional to the increase in demand, so this policy has not been fully implemented. Keywords: Implementation, Electric Motorbike Subsidy, Sustainable Environment.